2012
DOI: 10.2174/138161212799436485
|View full text |Cite
|
Sign up to set email alerts
|

Classes of Sigma2 (σ2) Receptor Ligands: Structure Affinity Relationship (SAfiR) Studies and Antiproliferative Activity

Abstract: Although several pieces of information are still missing about sigma-2 (σ2) receptor, the production of high affinity 2 receptor ligands allowed important acquisitions. Morphans such as CB64D and CB184 were the first truly σ2-selective ligands synthesized, and their use in cell cultures highlighted the relationship between σ2 receptors and cell proliferation, shedding light on important diagnostic and therapeutic potentials with which σ2 ligands are endowed. The most significant classes of compounds are herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 48 publications
(88 reference statements)
0
24
0
1
Order By: Relevance
“…Importantly, σ 2 receptors have been shown to exert antiproliferative effects towards tumor cells when activated with σ 2 agonists. Promising results have been also obtained in vivo by treatment of animal tumor xenografts with σ 2 agents (Abate et al, 2012a). Taken together these pieces of evidence make σ 2 proteins intriguing targets for tumor diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Importantly, σ 2 receptors have been shown to exert antiproliferative effects towards tumor cells when activated with σ 2 agonists. Promising results have been also obtained in vivo by treatment of animal tumor xenografts with σ 2 agents (Abate et al, 2012a). Taken together these pieces of evidence make σ 2 proteins intriguing targets for tumor diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Ligands presumed to activate sigma-2 receptors induce apoptotic cell death in cancer cell lines (Vilner et al, 1995a;Crawford and Bowen, 2002;Ostenfeld et al, 2005;Bowen, 2007;Abate et al, 2012;Zeng et al, 2012;Mach et al, 2013). Because of these aspects, the sigma-2 receptor has received growing attention as a potential target in cancer therapy, and efforts are in progress to elucidate the identity and function of this protein and to develop highly selective targeting ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Design and synthesis 1-Cyclohexyl-4-[3-(5-methoxy-1,2,3,4-tetrahydronaphthalen-1-yl)-n-propyl]piperazine (PB28, Scheme 2) is one of the highest affinity s 2 agonists known, [9] and several series of compounds were developed starting from this lead. In addition, a different series of fluorescent ligands were developed from its structure, and structure-affinity relationship (SAfiR) studies indicated the best position on PB28 to insert the fluorescent tag and the most appropriate linker to obtain optimal s 2 binding.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, when activated by specific ligands, s 2 receptors cause cell death through diverse pathways that appear to depend on the cell types and on the molecule types. [9] Caspase involvement, as well as autophagy and reactive oxygen species (ROS) have been reported for cell death mediated by s 2 ligands. [10][11][12][13] In order to fully understand the pharmaceutical potential of these proteins for both tumor diagnosis and therapy, more specific and powerful pharmacological tools are needed.…”
Section: Introductionmentioning
confidence: 99%